Subclinical executive function impairment in children with asymptomatic, treated phenylketonuria: A comparison with children with immunodeficiency virus. Issue 3 (19th May 2018) - Bisiacchi, Patrizia; Mento, Giovanni; Tarantino, Vincenza; Burlina, Alberto
ABSTRACT: In this study we compared the neuropsychological profile of phenylketonuria (PKU) and human immunodeficiency virus (HIV) to examine the specificity of the executive function (EF) impairment reported in these two patologies. A total of 55 age-matched children and adolescents were assessed, including 11 patients with PKU, 16 patients with HIV and 28 healthy controls, underwent a neuropsychological assessment. Although neither the PKU nor the HIV group scored below the normative ranges, both groups showed lower scores in neuropsychological tests engaging EFs than controls. In addition, compared to patients with PKU the HIV group performed significantly worse in the Trail-Making Test A, Corsi Span and Verbal Fluency. These findings suggest that EF impairments in PKU (a) are limited to EFs (i.e., working memory and attentional shifting), (b) are not simply due to generalized processing speed deficits and (c) overlap partially with EF impairments found in a chronic medical developmental disorder.